2018
DOI: 10.1097/mnh.0000000000000420
|View full text |Cite
|
Sign up to set email alerts
|

Source and microenvironmental regulation of erythropoietin in the kidney

Abstract: We hypothesize that REP cells are neuron-like setpoint providers and controllers, which integrate information about blood O2 concentration and local O2 consumption via tissue pO2, and combine these inputs with intrinsic negative feedback loops and perhaps tubular cross-talk, converging in Epo regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…To assess the regulation of endogenous HIF‐dependent gene expression by the HIs, secreted Epo protein levels were analyzed in the supernatant of Hep3B cells. Epo is almost exclusively regulated at the gene expression level through HIF . All pan‐ and PHD‐selective HIs increased Epo protein levels (Figure C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the regulation of endogenous HIF‐dependent gene expression by the HIs, secreted Epo protein levels were analyzed in the supernatant of Hep3B cells. Epo is almost exclusively regulated at the gene expression level through HIF . All pan‐ and PHD‐selective HIs increased Epo protein levels (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Epo is almost exclusively regulated at the gene expression level through HIF. 55 All pan-and PHD-selective HIs increased Epo protein levels ( Figure 2C). DM-NOFD treatment did not induce Epo ( Figure 2C).…”
Section: Hi Selectivity Adjusts Hif Inductionmentioning
confidence: 93%
“…The corticomedullary region showed the deepest drop in O 2 bioavailability, which may expand into the cortex upon decreased tissue oxygenation, a prerequisite for the recruitment of additional REP cells. 61 Our animal model allowed for the conditional tagging of acutely recruited REP cells, whereas in previously established constitutively Cre-driven REP models it remained unknown whether labeled REP cells were still active. 8,12,39,62 Wholegenome sequencing of 2 Epo-Cre ERT2 founder strains revealed that 45.9 kb 5' and 52 kb 3' flanking regions are sufficient to confer accurate tissue-specific and oxygenregulated Epo gene expression in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…If Hgb was not measured in this period, the follow up started following the first recorded Hgb measurement after Jan 1st 2009. For incident severe CKD patients, follow up began on the date of the second measurement showing an eGFR < 30 mL/min/1.73 m 2 after Jan 1st 2009 if Hgb measurements were recorded within 1 year before that date. For these patients, anemia grade was determined based on the lowest Hgb recording during that year.…”
Section: Anemiamentioning
confidence: 99%
“…Anemia is common in patients with chronic kidney disease (CKD) and prevalence increases with CKD severity [1]. Renal erythropoietin-producing cells sense low tissue oxygen tension and respond by the production of erythropoietin, a hormone that stimulates red blood cell production [2]. CKD leads to a disruption of this process, erythropoietin deficiency and subsequent anemia, characterized by lower than normal number of circulating red blood cells or decreased levels of hemoglobin (Hgb) [3].…”
Section: Introductionmentioning
confidence: 99%